1994
DOI: 10.1111/j.1365-2222.1994.tb02725.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive assessment of bronchial inflammation in asthma: no correlation between eosinophilia of induced sputum and bronchial responsiveness to inhaled hypertonic saline

Abstract: Bronchial inflammation in mild asthma has been investigated using bronchoscopical techniques. The safety of bronchoscopy in patients with more severe asthma has been questioned. We have used the non-invasive technique of hypertonic saline (HS) inhalation to induced sputum samples for cellular analysis whilst simultaneously yielding a measure of bronchial responsiveness. Ten normal subjects and a heterogenous group of 24 asthmatic patients (range % predicted FEV1 43.3-111.5) underwent HS challenge. Sputum sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
63
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 22 publications
4
63
3
Order By: Relevance
“…In addition, eosinophils in sputum are associated with bronchial hyperresponsiveness (BHR) when measured by methacholine [14] or histamine [15], but not by hypertonic saline [16]. Moreover, it has been shown in subjects with asthma that eosinophil numbers in sputum reflect those in bronchial washings, bronchoalveolar lavage fluid, and bronchial biopsies [17,18].…”
mentioning
confidence: 99%
“…In addition, eosinophils in sputum are associated with bronchial hyperresponsiveness (BHR) when measured by methacholine [14] or histamine [15], but not by hypertonic saline [16]. Moreover, it has been shown in subjects with asthma that eosinophil numbers in sputum reflect those in bronchial washings, bronchoalveolar lavage fluid, and bronchial biopsies [17,18].…”
mentioning
confidence: 99%
“…[12][13][14][15] In many studies, however, the level of significance of the interrelations among all these outcome measures has been found to be clinically irrelevant. [16][17][18][19][20] In this regard we have recently found that sputum measurements of eosinophilic inflammation do not accurately reflect current clinical indices of asthma severity in patients with chronic, stable asthma 12 and might therefore provide complementary data for monitoring of the disease.…”
mentioning
confidence: 99%
“…Examination of spontaneous or induced sputum promises to be a reliable direct method by which this can be achieved noninvasively [2][3][4][5][6][7][8].…”
mentioning
confidence: 99%